Preliminary study of a novel method for conveying corrected image volumes in surgical navigation. Issue 1 (18th September 2012) - Simpson, Amber L.; Dumpuri, Prashanth; Ondrake, Janet E.; Weis, Jared A.; Jarnagin, William R.; Miga, Michael I.
Abstract Background Commercial image‐guided surgery systems rely on the fundamental assumption that preoperative medical images represent the physical state of the patient in the operating room. The guidance display typically consists of a three‐dimensional (3D) model derived from medical images and three orthogonal views of the imaging data. A challenging question in image‐guided surgery is: what happens when the images used in the guidance display no longer correspond to the current geometric state of the anatomy and guidance information is still desirable? Methods We modify the conventional display with two techniques for incorporating a displacement field from a finite‐element model into the guidance display and present a preliminary study of the effect of our method on performance with a simple surgical task. The topic of this paper is methods for conveying the computational model solution, not the model itself. To address the integration of the computational model solution into the display, a novel method of applying the deformation to the tool tip was developed, which quickly corrects for deformation but also maintains the pristine nature of the preoperative images. We compare the proposed technique to an existing method that applies the deformation field to the image volume. Results A pilot study compared mean performance with our method of applying the deformation to the tool tip and the conventional technique. These methods were statistically similar with respect to accuracy of localization (p < 0.05) and amount of time (p < 0.05) required for localization of the target. Conclusions These results suggest that our new technique can be used in place of the computationally expensive task of deforming the image volume, without affecting the time or accuracy of the surgical task. Most notably, our work addresses the problem of incorporating deformation correction into the guidance display and offers a first step toward understanding its effect on surgical performance. Copyright © 2012 John Wiley & Sons, Ltd.